Age-dependent decline in learning and memory performances of WAG/Rij rat model of absence epilepsy - ARICIOĞLU, FEYZA (BMC, 2012)
Recent clinical studies revealed emotional and cognitive impairments associated with absence epilepsy. Preclinical research with genetic models of absence epilepsy however have primarily focused on dysfunctional emotional processes and paid relatively less attention to cognitive impairment. In order to bridge this gap, we investigated age-dependent changes in learning and memory performance, anxiety-like behavior, and locomotor activity of WAG/Rij rats (a valid model of generalized absence epilepsy) using passive avoidance, Morris water maze, elevated plus maze, and locomotor activity cage. We tested 5 month-old and 13 month-old WAG/Rij rats and compared their performance to age-matched Wistar rats. Results revealed a decline in emotional and spatial memory of WAG/Rij rats compared to age-matched Wistar rats only at 13 months of age. Importantly, there were no significant differences between WAG/Rij and Wistar rats in terms of anxiety-like behavior and locomotor activity at either age. Results pointed at age-dependent learning and memory deficits in the WAG/Rij rat model of absence epilepsy.
Keywords: Anxiety; Learning; Locomotor Activity; Memory; Rats; WAG/Rij; Wistar; TEMPORAL-LOBE EPILEPSY; 2-WAY ACTIVE-AVOIDANCE; SPIKE-WAVE DISCHARGES; NONCONVULSIVE EPILEPSY; PASSIVE-AVOIDANCE; ANIMAL-MODELS; WISTAR RATS; NEW-ONSET; CHILDHOOD; BEHAVIOR